Proses Manajemen Sarana dan Prasarana di Madrasah Aliyah Negeri - Noven, Tanti Tri Aulia; Inayati, Nurul Latifatul (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
Infrastructure and facilities for education are essential components that enable the application of learning. Therefore, effective management is essential. Madrasah Aliyah Negeri 2 Surakarta exemplifies this by prioritizing the management process of facilities and infrastructure to enhance the learning environment. This emphasis is why research fine it compelling to conduct studies at Madrasah Aliyah Negeri 2 Surakarta. This study’s goal is to provide an overview of Madrasah Aliyah Negeri 2 Surakarta’s facilities and infrastructure management procedure. The research employs a phenomenological approach with data collection techniques such as interview, observation, and documentation. The study’s findings indicate that, in general, the management of facilities and infrastructure at Madrasah Aliyah Negeri 2 Surakarta involves four processing: planning, inventory or recording, maintenance, and removal. Planning occurs through joint meetings, while inventory is conducted by the vice principal of the facilities and infrastructure by recording and coding items, which are then reported to relevant parties. Maintenance is a collaborative effort among all school members to ensure the constant of goods for use. The removal of facilities and infrastructure is executed through three methods: auctioning, grants, and destruction.